The consumption of ritual and the changing values of filial piety in ancestor worship - Cao, Meng (The Australian journal of anthropology, 2023)
Ancestor worship is regarded as the key element of the Han people's belief system across most of China. However, the rituals pertaining to death, such as in funerals and annual ancestor worship, vary from place to place. For decades, the state has made tremendous efforts to reform and standardise funerals consistent with its path to modernization by insisting on more socialist practices rather than those that are perceived as ‘superstitious’ and ‘irrational’, such as burning paper and incense or performing rituals. I argue that despite regulating the use of funeral materials or memorial types, the state has failed to reform the essence of death rituals, that is, the duty of filial piety and people's conception of the afterlife. In addition, funerals and other rituals related to death contribute to individual's social reputation.